2015
DOI: 10.3390/environments2040435
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Preparedness: A Knowledge and Attitudes Study in Southern Nigeria

Abstract: Global climate change is projected to adversely impact freshwater resources, and in many settings these impacts are already apparent. In Nigeria, these impacts can be especially severe because of limited adaptive capacity. Understanding the knowledge and attitudes of current and future Nigerian decision-makers is important to preparing Nigeria for climate change impacts. This paper examines the knowledge and attitudes of university students and government officials about the causes, effects, and priority given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 13 publications
4
34
3
Order By: Relevance
“…Watkins [5], for instance, argued that public perception can significantly influence future development and environmental policies. In this regard, public perceptions, awareness and knowledge of climate change have received increased attention in the literature in recent times [6][7][8][9][10][11][12][13][14][15]. It is argued that individual behaviour is central to climate change because individuals influence large procedures of change and policy decisions [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watkins [5], for instance, argued that public perception can significantly influence future development and environmental policies. In this regard, public perceptions, awareness and knowledge of climate change have received increased attention in the literature in recent times [6][7][8][9][10][11][12][13][14][15]. It is argued that individual behaviour is central to climate change because individuals influence large procedures of change and policy decisions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst these studies present insights about students' knowledge of climate change, key issues such as involving knowledge on indirect causes (such as meat consumption) and effects (such as conflicts and gender inequalities) of climate change were not explored. Also, students participation in climate change workshops and their membership of environment-related student clubs influence their knowledge of climate change needs further inquiry [7]. Improving students' knowledge of climate change can help to raise awareness of the phenomenon in society as a whole [27].…”
Section: Introductionmentioning
confidence: 99%
“…It would seem, from this, that they required more information. Researchers have also shown that awareness of climate change among students is influenced by access to information, by media coverage of the issue, by advocacy, and by the level of environmental concern (Carr, 2015;Christensen & Knezek, 2015;Ojomo, Elliott, Amjad & Bartram, 2015). At the Copperbelt University, it was therefore important to explore the awareness and attitudes of students regarding climate change.…”
Section: Sustainability and Climate Change Awareness In Universitiesmentioning
confidence: 99%
“…Students were used as part of the sample because they are an important group in the society and they are, or will be, in the near future, players in the housing market, so their attitude toward housing-related health risks influences their house buying and maintenance behaviors. It is not rare to find samples made of students within the field of attitude studies [54][55][56][57]. The results cannot be extrapolated to the entire Romanian population, but they may serve as a reference point in the elaboration of future research dedicated to radon.…”
Section: Methodsmentioning
confidence: 99%